Comparison of Acute Complications of Single Staged vs. Two Staged Hypospadias Repair - Haider, Syed Muhammad; Shahbazi, Hamza Khan; Muhammad Shadman, Muhammad Shadman; Khan, Fahimullah; Ahmad, Shahzad; Fayyaz, Hamza (Journal of Postgraduate Medical Institute, 2025)
Objective: To compare the immediate and early complications (till 4 weeks post op) of single staged versus two staged hypospadias repairs. Methodology: This study was carried out at Department of plastic surgery, Hayatabad Medical Complex Peshawar from 18-02-2020 to 18-08-2020., which included 60 patients undergoing hypospadias repair. Patients in group A underwent a single staged repair, while those in group B underwent two staged repair. Data was collected during postoperative follow-up visits. Data collection included patient demographics and complication rate (infection, wound dehiscence and meatal stenosis). Results: A total of 8.3% of the overall sample developed infection, 15% wound dehiscence and 8.3% meatal stenosis. In group A, 13.3% developed infection compared to 3.3% in group B (p 0.161), 20% in group A developed wound dehiscence compared to 10% in group B (p 0.278) and 10% in group A developed meatal stenosis compared to 6.7% in group B (p 0.64). Conclusion: Although, the children in double staged repair group developed less no of complications than single staged group, the difference was not statistically significant. Two staged repair is a preferred choice for repair of hypospadias due to lower frequency of complications and better cosmetic results compared to single stage.